Risk Behavior for Pesticide Exposure in Children living in Agricultural Area - Ibrahim, Ilyas; Sillehu, Sahrir (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Chemical pesticides are mixtures of chemicals used to control or kill pests. Pesticides are often used in agriculture to maintain and increase agricultural production, but have a negative impact on the environment and public health. Children who live in agricultural areas are a group at risk of exposure to pesticides due to activities such as playing and participating in agricultural activities. The purpose of this study was to identify the behavior at risk of exposure to pesticides in children in the agricultural area of ​​Bulakamba District. This type of research is descriptive with a cross-sectional study design. The research variable is the identification of behavior at risk of exposure to pesticides in children. The subjects of the study were elementary school students in the Bulakamba district as many as 48 students. Data were collected by interview, observation, and examination of pesticide metabolites in students' urine. . The results showed that of the 48 students exposed to pesticides, 17 students were positive for pesticide metabolites and 31 students were negative. Risk behavior is the work of parents as farmers from 19 students there are 10 students who are positively exposed to pesticides, the habit of playing in agricultural areas from 18 students there are 11 students who are exposed to pesticides, the habit of helping with agricultural activities from 15 students there are 10 students positive for pesticides and the habit of storing pesticides in the home environment of 21 students there are 11 students positively exposed to pesticides.